In-depth structural characterization of oligosaccharides released by GH107 endofucanase MfFcnA reveals enzyme subsite specificity and sulfated fucan substructural features. (4th December 2021) - Ropartz, David; Marion, Lery; Fanuel, Mathieu; Nikolic, Jasna; Jam, Murielle; Larocque, Robert; Ficko-Blean, Elizabeth; Michel, Gurvan; Rogniaux, Helene
Abstract: The extracellular matrix of brown algae represents an abundant source of fucose-containing sulfated polysaccharides (FCSPs). FCSPs include sulfated fucans, essentially composed of fucose, and highly heterogeneous fucoidans, comprising various monosaccharides. Despite a range of potentially valuable biological activities, the structures of FCSPs are only partially characterized and enzymatic tools leading to their deconstruction are rare. Previously, the enzyme Mf FcnA was isolated from the marine bacterium Mariniflexile fucanivorans and biochemically characterized as an endo-α-1 → 4-l -fucanase, the first member of glycoside hydrolase family 107. Here, Mf FcnA was used as an enzymatic tool to deconstruct the structure of the sulfated fucans from Pelvetia canaliculata (Fucales brown alga). Oligofucans released by Mf FcnA at different time points were characterized using mass spectrometry coupled with liquid chromatography and tandem mass spectrometry through Charge Transfer Dissociation. This approach highlights a large diversity in the structures released. In particular, the analyses show the presence of species with less than three sulfates per two fucose residues. They also reveal species with monosaccharides other than fucose and the occurrence of laterally branched residues. Precisely, the lateral branching is either in the form of a hexose accompanied by a trisulfated fucose nearby, or of a side chain of fucoses with a pentose as the branching point on the polymer. Overall, the results indicate that the structure of sulfated fucans from P. canaliculata is more complex than expected. They also reveal the interesting capacity of Mf FcnA to accommodate different substrates, leading to structurally diverse oligofucan products that potentially could be screened for bioactivities.